Multidirectional Dynamic Response and Swing Shedding of Grapes: An Experimental and Simulation Investigation under Vibration Excitation - Po Zhang; De Yan; Xiaona Cai; Youbin Chen; Lufeng Luo; Yaoqiang Pan; Xiangjun Zou (Agronomy, 2023)
During mechanized table grape harvesting, berries are subjected to vibration and collision, which can cause shedding and damage to the fruit. Research on table grape berry shedding has primarily focused on macroscopic swing modes, which are reflected in the integrated grape cluster structure and idealized particle interactions, as well as static response treatments. However, these approaches are unable to accurately explain the characteristics of berry wobbling during picking, predict shedding-prone areas, or identify factors affecting shedding. In this paper, we study the dynamic response characteristics of grape berries in the X, Y, and Z directions by establishing a dynamic model and combining harmonic response and random vibration characteristics with finite element analysis. Our studies revealed that grape berries exhibit various forms (swinging and rebounding) under the same stimulus during harvesting. The grape berry amplitude in the X, Y, and Z directions were 14.71, 12.46, and 27.10 mm, respectively, with the most obvious response being in the Z direction and the flattest response in the Y direction. Berries in the lower cob system part were relatively stable, while those in the upper right side were more prone to swinging and falling, with areas most likely to fall off concentrated in the upper right side. This system accurately predicted the dynamic response characteristics of fruit during vibration harvesting and provided an ideal basis for mechanized grape harvesting. Optimization and research on fruit collection equipment may benefit from this theoretical basis.